Vispārējo izglītību reglamentējošo normatīvo prasību izpildes nodrošināšana. - Bredika, Inta (Latvijas Universitāte, 2006)
Maģistra darbs “ Vispārējo izglītību reglamentējošo normatīvo prasību izpildes nodrošināšana” izstrādāts studiju programmas “Izglītības zinātņu” ietvaros izglītības vadības studiju virzienā. Teorētiski pētnieciskās darba daļas izstrādes rezultātā tapusi jēdzienu „regulējošās normatīvās prasības” un „skolvadība” definīcijas, izstrādāti normatīvo prasību izpildes nodrošināšanas posmi. Katra pētījuma posma beigās apkopoti un izvērtēti pētījumā iegūtie rezultāti un formulēti secinājumi. Darba noslēgumā izstrādāti priekšlikumi izglītības iestāžu vadītāju darba traucējošo faktoru ietekmes mazināšanai nodrošinot normatīvo prasību izpildi. Pētījuma noslēgumā ir ieskicēts arī tālākais pētnieciskā darba virziens – metodikas izstrāde regulējošo normatīvo prasību un iekšējo normatīvo aktu izstrādei.

The Master’s Degree work „Ensuring the implementation of the general regulatory normative requirements” has been worked out under the studies program "Educational Science" in the sphere of the education management studies. Developing the theoretical research part of the work the definitions of the terms "regulatory normative requirements" and "school management" have been formulated and the stages of the ensuring the implementation of the normative requirements have been worked out. Therefore the first task of the research has been completed. The conclusions have been formulated and the further research actions have been corrected. Though the evaluation of the offer of the courses states that the offered knowledge and skills have to ensure the skills of the headmasters working with the normative documents, yet the interrogation of the headmasters states the contrary. In the conclusion the further direction of the research is outlined – development of procedure to work out the regulative normative requirements and inner normative documents.
Ensuring the implementation of general regulatory normative requirements.
Keywords: Pedagoģija